The Role of Core Marketing Capability in the Relationship between Marketing Competitive Curriculum and Marketing Employability Performance - Andi Setiawan; Riyadi, Riyadi; Sri Wahyuni; Saptianing, Saptianing (International Journal of Education, Vocational and Social Science, 2023)
This study aims to deepen understanding of the practice of core marketing capability by exploring the impact of marketing competitive curriculum and marketing employability performance for vocational high education graduates in carrying out multiplier tasks. Core marketing capability is proposed to bridge the relationship between competitive marketing curriculum and marketing employability performance. The study is a survey design approach, data collected from 225 respondents were analyzed through structural equation modeling using AMOS 26.0. The findings of this study reveal a significant relationship between marketing competitive curriculum directly with marketing employability performance, and indirectly through Core Marketing Capability